Effect of Red Bull on Histology of Renal Mesangium - Ammara Rasheed, Mohtasham Hina, Muhammad Rizwan Bashir Kiani, Raafea Tafweez, Imtiaz Aslam, Arslan Akbar Saeed, Ammara Rasheed, Mohtasham Hina, Muhammad Rizwan Bashir Kiani, Raafea Tafweez, Imtiaz Aslam, Arslan Akbar Saeed (Journal of Rawalpindi Medical College, 2021)
Objective: To determine the consequences of energy drink (Red bull) on renal mesangium of albino rats. Materials and Methods: This study was carried out at the Anatomy Department of King Edward Medical University, Lahore, from August 2018 to December 2019. It was an experimental randomized controlled trial. Total 90 adult albino male rats, 8-12 weeks old, weighing 130 to 160 grams were taken. Healthy animals were included. Rats were divided into three groups Group A and B experimental groups received 1.5ml/kg and 2.2ml/kg body weight of red bull energy drink, respectively. Group C received 1ml/kg body weight of distilled water. Results: The mean initial and final weight of animals was around 150g and 170g, respectively. The mean paired kidney weight and relative tissue weight index for all three groups were found insignificant. Microscopic examination showed mesangial hypercellularity and vascular congestion in renal cortex of groups A and B, none in group C. These were significant among two experimental groups with a p-value less than 0.001. Conclusion: It was found that the use of energy drinks induces histopathological changes in the renal mesangium.